Economic Issues on Food Safety - Adinolfi, Felice (Ital J Food Saf, 2016)
A globalised food trade, with a huge increase of the exchanged volume, extensive production and complex supply chains are contributing towards an increased number of microbiological food safety outbreaks. All of these factors are putting pressure on the stakeholders, either public or private, in terms of rule and control. In fact, this scenario could force manufacturers to be lenient towards food safety control intentionally, or unintentionally, and result in a major foodborne outbreak that causes health problems and economic loss. As a response to emerging calls for the adoption of a systemic approach to food safety, we try to identify and discuss the several related economics issue in this field. Based on an extensive analysis of academic and policy literatures on the economic effects of global environmental change at different stages of the food system, we highlight the main issues involving economists in the field of food safety. In the first part, we assessed the several approaches and problems related to the evaluation of food safety improvements, followed by an overview of drivers of food safety demand in the second part. The third section is devoted to discussing changes occurred at the institutional level in building and managing food safety policies. The last section summarises the main considerations aroused from the work.